Osteology and cranial musculature of Caiman latirostris (Crocodylia: Alligatoridae) - Bona, Paula (2011)
Caiman latirostris Daudin is one of the extant species of Caimaninae alligatorids characterized taxonomically only by external morphological features. In the present contribution, we describe the cranial osteology and myology of this species and its morphological variation. Several skull dissections and comparisons with other caimans were made. Although jaw muscles of living crocodiles show the same general “Bauplan” and alligatorids seem to have a similar cranial musculature pattern, we describe some morphological variations (e.g., in C. latirostris the superficial portion of the M. adductor mandibulae externus did not reach the postorbital; the M. adductor mandibulae internus pars pterygoideus dorsalis did not reach the pterygoid and lacrimal and contrary to the case of C. crocodilus the M. adductor mandibulae internus pars pterygoideus ventralis attaches to the posterodorsal surface of the pterygoid and the pterygoid aponeurosis, without contacting the dorsal and ventral surface of the pterygoid margin; the M. intermandibularis is attached to the anterior half of the splenial and posteriorly inserts medially by a medial raphe that serves as attachment zone for M. constrictor colli, and the M. constrictor colli profundus presents a medial notch in its anterior margin). In addition, the skull of C. latirostris differs from that of other caimans and possesses several characters that are potential diagnostic features of this species (e.g., outline of glenoid cavity in dorsal view, extension of the rostral ridges, and occlusion of the first dentary tooth). Nevertheless, these characters should be analyzed within the phylogenetic context of the Caimaninae to evaluate its evolutionary implications for the history of the group. J. Morphol.